PROSPECTS OF APPLICATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN TRADE UNION ACTIVITIES (World Economics and Finance Bulletin, 2026)
The article analyzes the prospects for the application of artificial intelligence (AI) technologies in the activities of trade unions. In the conditions of the modern digital economy, trade unions can use AI technologies to effectively communicate with their members, predict labor disputes, conduct intellectual analysis of collective agreements, and scientifically substantiate management decisions. The study identifies the main directions for introducing chatbots, natural language processing, machine learning algorithms, and forecasting models into the activities of trade unions based on international experience. It also examines the risks of introducing AI technologies and measures to eliminate them. The article provides practical recommendations for the digital transformation of trade unions.
Keywords: artificial intelligence; trade unions; digital transformation